2022
DOI: 10.1038/s41598-022-27171-1
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent biological toxicity of green synthesized silver nanoparticles in rat’s brain

Abstract: Metal nanoparticles, in general, and silver nanoparticles (AgNPs), in particular, have been the focus of numerous studies over the last two decades. Recently, the green synthesis of metal nanoparticles has been favored over chemical synthesis due to its low toxicity and easy preparation. The present study aims to investigate the dose-dependent toxicity of green synthesized AgNPs on rats’ brains. Thirty-four Wistar male rats were divided into four groups. The first, second, and third groups were administered fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Therefore, 5H-T and norepinephrine have been significantly reduced at the high dose of 10 mg kg. It is known that alterations in monoamine neurotransmitters may be involved in many neurological disorders [ 31 ]. More exploration on rat's brains found AgNPs impaired mitochondrial function through autophagy even with a low dose (0.2 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 5H-T and norepinephrine have been significantly reduced at the high dose of 10 mg kg. It is known that alterations in monoamine neurotransmitters may be involved in many neurological disorders [ 31 ]. More exploration on rat's brains found AgNPs impaired mitochondrial function through autophagy even with a low dose (0.2 mg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…The authors confirmed that the cytotoxic oxidative changes induced by the biogenic AgNPs were minimal. This was due to the availability of capping, biocompatible, and enhancing molecules on the synthesized biogenic AgNPs [176].…”
Section: Toxicity Of Biogenic Agnpsmentioning
confidence: 99%
“…Geometric intricacies, encompassing irregular shapes, surface charge, and Zeta potential, contribute to distinctive interactions with cellular entities, resulting in mechanical damage and overall toxicity [ 19 ]. Notably, the synthesis method plays a significant role, with green-synthesized AgNPs generally demonstrating lower cytotoxicity than their chemically synthesized counterparts [ 20 ]. The nature of silver usage is also dose-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of silver usage is also dose-dependent. Low concentrations exhibit beneficial effects, while prolonged exposure to increasing concentrations escalates the toxicity of AgNPs [ 20 ]. Another critical factor impacting the toxicity of silver nanoparticles is their oxidation potential [ 21 ] and the subsequent release of Ag + ions.…”
Section: Introductionmentioning
confidence: 99%